Clinical Characteristics and Stage at Presentation of Glaucoma Patients in Sub-Saharan Africa. Issue 9 (27th September 2022) - Olawoye, Olusola; Kizor-Akaraiwe, Nkiru; Pons, Jonathan; Sarimiye, Tarela; Washaya, Jennifer; Hughes, Sowunmi; Ashaye, Adeyinka; Garba, Farouk; Gessesse, Girum W.; Chitedze, Richard; Ibanga, Affiong; Saka, Vincent; et al.
Abstract : Précis: The initial presentation of glaucoma varies meaningfully across SSA. A comprehensive strategy with regional customization based on local differences is needed to reduce glaucoma blindness in SSA. Purpose: To explore regional variations in the presentation of newly diagnosed glaucoma in Sub Saharan Africa (SSA). Methodology: This was a multicenter, cross-sectional study in which newly diagnosed, consecutive, glaucoma patients aged older than or equal to 18 years were recruited from 27 eye clinics in 10 countries throughout SSA. Demographic and ophthalmic examination data were collected. Glaucoma severity was based on optic nerve head and visual field assessment. Statistical analyses were performed using STATA version 14.0. Results: Among 1214 enrolled patients with newly diagnosed glaucoma from Western, Eastern, and Southern Africa, the overall mean (SD) age was 59.9 (17.1) years. More than half of all patients (716/1178; 60.8%) presented with severe glaucoma in the worse eye, and one-third (36.9%) had severe glaucoma in both eyes. Primary open angle glaucoma was the commonest form of glaucoma in all regions (77.4%). A family history of blindness (260/1204, 21.6%) was common. Patients from Western Africa had lower mean presenting intraocular pressure (26.4 [11.1] mm Hg, P <0.001), but had worse glaucoma in the better eye based on mean cup-disc ratio (0.8; P <0.001) and mean visual field mean deviation [10.4 (8.4)] dB, P =0.016) compared with other regions. Exfoliation glaucoma was more common in Eastern Africa (30/170=17.7%, P <0.001) compared with other regions. Conclusion: The initial presentation of glaucoma varies meaningfully across SSA. A comprehensive strategy with regional customization based on local differences is needed to reduce glaucoma blindness in SSA.